Is adolescence the missing developmental link in Microbiome–Gut–Brain axis communication?. Issue 5 (28th January 2019) - Flannery, Jessica; Callaghan, Bridget; Sharpton, Thomas; Fisher, Philip; Pfeifer, Jennifer
Abstract: Gut microbial research has recently opened new frontiers in neuroscience and potentiated novel therapies for mental health problems (Mayer, et al., 2014). Much of our understanding of the gut microbiome's role in brain function and behavior, however, has been largely derived from research on nonhuman animals. Even less is known about how the development of the gut microbiome influences critical periods of neural and behavioral development, particularly adolescence. In this review, we first discuss why the gut microbiome has become increasingly relevant to developmental cognitive neuroscience and provide a synopsis of the known connections of the gut microbiome with social–affective brain function and behavior, specifically highlighting human developmental work when possible. We then focus on adolescence, a key period of neurobiological and social–affective development. Specifically, we review the links between the gut microbiome and six overarching domains of change during adolescence: (a) social processes, (b) motivation and behavior, (c) neural development, (d) cognition, (e) neuroendocrine function, and (f) physical health and wellness. Using a developmental science perspective, we summarize key changes across these six domains to underscore the promise for the gut microbiome to bidirectionally influence and transform adolescent development.